A zebrafish model of PMM2-CDG reveals altered neurogenesis and a substrate-accumulation mechanism for N-linked glycosylation deficiency - Cline, Abigail (The American Society for Cell Biology, 2012)
Congenital disorder of glycosylation (PMM2-CDG) results from mutations in pmm2, which encodes the phosphomannomutase (Pmm) that converts mannose-6-phosphate (M6P) to mannose-1-phosphate (M1P). Patients have wide-spectrum clinical abnormalities associated with impaired protein N-glycosylation. Although it has been widely proposed that Pmm2 deficiency depletes M1P, a precursor of GDP-mannose, and consequently suppresses lipid-linked oligosaccharide (LLO) levels needed for N-glycosylation, these deficiencies have not been demonstrated in patients or any animal model. Here we report a morpholino-based PMM2-CDG model in zebrafish. Morphant embryos had developmental abnormalities consistent with PMM2-CDG patients, including craniofacial defects and impaired motility associated with altered motor neurogenesis within the spinal cord. Significantly, global N-linked glycosylation and LLO levels were reduced in pmm2 morphants. Although M1P and GDP-mannose were below reliable detection/quantification limits, Pmm2 depletion unexpectedly caused accumulation of M6P, shown earlier to promote LLO cleavage in vitro. In pmm2 morphants, the free glycan by-products of LLO cleavage increased nearly twofold. Suppression of the M6P-synthesizing enzyme mannose phosphate isomerase within the pmm2 background normalized M6P levels and certain aspects of the craniofacial phenotype and abrogated pmm2-dependent LLO cleavage. In summary, we report the first zebrafish model of PMM2-CDG and uncover novel cellular insights not possible with other systems, including an M6P accumulation mechanism for underglycosylation.